Remote Work and Digital Progressions during the Covid-19 Pandemic for Auditors and Financial Managers in Johannesburg, South Africa - Irene Marindi (The Thinker)
The emergence of the Fourth Industrial Revolution (4IR) marks a significant transformation, introducing technological and digital advancements that are reshaping how work is conducted, largely through virtual platforms (Abe 2020: xviii). This shift is altering both the nature of work and traditional workplace concepts. While research acknowledges developments across various employment sectors, the increasing reliance on virtual arrangements has yielded mixed outcomes. This paper argues that the 4IR, coupled with the Covid-19 pandemic, has blurred the boundaries between physical and virtual work environments, often rendering physical workplaces less relevant. This transformation holds the potential to significantly impact worker engagement and well-being. Using a qualitative research approach, 26 interviews were conducted with auditors and financial managers in Johannesburg-based firms. The exploratory findings revealed that the Covid-19 pandemic accelerated the adoption of digital accounting practices for auditors and financial managers working remotely. Moreover, working from home was a double-edged sword for the participants in this study, as they compared their experiences during and before the pandemic. The findings demonstrate that digital processing dictates how work is conducted in the accounting and financial sectors.